2015
DOI: 10.1038/srep12614
|View full text |Cite
|
Sign up to set email alerts
|

One-step biosynthesis of α-ketoisocaproate from l-leucine by an Escherichia coli whole-cell biocatalyst expressing an l-amino acid deaminase from Proteus vulgaris

Abstract: This work aimed to develop a whole-cell biotransformation process for the production of α-ketoisocaproate from L-leucine. A recombinant Escherichia coli strain was constructed by expressing an L-amino acid deaminase from Proteus vulgaris. To enhance α-ketoisocaproate production, the reaction conditions were optimized as follows: whole-cell biocatalyst 0.8 g/L, leucine concentration 13.1 g/L, temperature 35 °C, pH 7.5, and reaction time 20 h. Under the above conditions, the α-ketoisocaproate titer reached 12.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…As an alternative, Corynebacterium glutamicum was genetically engineered to synthesize α‐KIC, yielding a titer of only 9.23 g L −1 . Recently, 69.1 g L −1 α‐KIC has been efficiently synthesized at a 50.3 % conversion rate by expressing L‐AAD derived from Proteus vulgaris in E. coli BL21, followed by an attempt to optimize protein expression levels; however, α‐KIC titer only increased to 86.55 g L −1 within 20 h . In addition, although the procedure for synthesizing α‐KMV using amino acid oxidase has been briefly outlined, the yield is very low (less than 10 g L −1 ) .…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative, Corynebacterium glutamicum was genetically engineered to synthesize α‐KIC, yielding a titer of only 9.23 g L −1 . Recently, 69.1 g L −1 α‐KIC has been efficiently synthesized at a 50.3 % conversion rate by expressing L‐AAD derived from Proteus vulgaris in E. coli BL21, followed by an attempt to optimize protein expression levels; however, α‐KIC titer only increased to 86.55 g L −1 within 20 h . In addition, although the procedure for synthesizing α‐KMV using amino acid oxidase has been briefly outlined, the yield is very low (less than 10 g L −1 ) .…”
Section: Resultsmentioning
confidence: 99%
“…After optimizing the conditions with response service methodology, the maximal α-KIC production reached 1.2 g/L [17,39]. A similar approach was used by Song et al (2015) to produce α-KIC, but in this case, an E. coli whole-cell biocatalyst, expressing an L-AAD, EC 1.4.3.2 from Proteus vulgaris, was used. The membrane-bound L-AAD from P. vulgaris is an oxidoreductase with flavin adenine dinucleotide as a coenzyme, which catalyze the deamination of the deamination of L-leucine to KIC.…”
Section: Phenylpyruvic Acidmentioning
confidence: 99%
“…The catalysis occurs via the binding of Proteus L-AADs to the electron transport chain to reduce O 2 to H 2 O. After optimizing the reaction conditions and the substrate feeding strategy, the α-KIC titer reached 69.1 g/L with a substrate conversion rate of 50.3% [40]. However, the α-KIC production was low, because of feedback reactions that limited its production.…”
Section: Phenylpyruvic Acidmentioning
confidence: 99%
“…l‐AADs from P. mirabilis catalyze stereospecific oxidative deamination of l ‐amino acids with formation of their respective keto acids and ammonia without production of hydrogen peroxide (Geueke and Hummel, ). In previous studies, we used FAD‐dependent l ‐AADs from Proteus species to produce a series of α‐keto acids, including phenylpyruvic acid (PPA) (Hou et al, , ), α‐ketoglutaric acid (α‐KG) (Hossain et al, ,), α‐ketoisocaproate (KIC) (Song et al, ), and keto‐γ‐methylthiobutyric acid (KMTB) (Hossain et al, ). We found that the supply of FAD is a limiting step in the catalysis driven by l ‐AAD.…”
Section: Introductionmentioning
confidence: 99%